Delineation of EMS-induced genetic variability in some agronomic traits in mungbean, Vigna radiata (L.) Wilczek. - Singh, Rupinder; Agarwal, M.; Kole, C. R. (Plant Breeding and Seed Science, 2008)
The investigation involved treatment of pre-soaked seeds (11h) of a mungbean cutivar, PUSA 9072 with five doses of ethyl methane suphonate (EMS) at 0.1, 0.25, 0.5, 0.75 and 1% for 4hr under dark. Observation on field grown mutagenized population with regard to 14 agronomic characters evidenced for induction of the variability in the M1 generation itself. The CV values of the traits for mutagenised population were stupendously higher for most of the test characters to the tune of 57% cases as compared to the untreated (control) plants...